Utilizing NeuroTouch, a virtual reality simulator, to assess and monitor bimanual performance during brain tumor resection. (3rd June 2015) - Alotaibi, FE; Del Maestro, R; AlZhrani, G; Mullah, MA; Sabbagh, A; Azarnoush, H; Winkler-Schwartz, A
Abstract : Background: NeuroTouch simulator provides the potential to determine performance metrics, but validation and easily utilized software are essential before implementation of this platform into neurosurgical training. Objectives: Evaluate and validate neurosurgical performance metrics for simulated brain tumors resection. Develop software and a global web based system to allow utilization of these metrics. Methods: The bimanual resection of 8 simulated brain tumors with differing complexity was evaluated. Software was developed to automatically generate all the metrics from NeuroTouch data output including: blood loss, tumor percentage resected, total brain volume removed, maximum and sum of forces utilized, efficiency index, ultrasonic aspirator path length index (UAPLI), coordination index and ultrasonic aspirator bimanual forces ratio (UABFR). Six neurosurgeons and 12 residents were evaluated. Results: Resident performance was significantly more impaired than neurosurgeon by increasing tumor complexity. Significant differences were found between neurosurgeons, senior, and junior residents on efficiency index and UAPLI. UABFR outlined significant differences between senior and junior residents. Coordination index demonstrated significant differences between junior residents and neurosurgeons. Conclusions: Utilizing metrics employed the NeuroTouch platform differentiated novice from expert performance. Software was developed for metrics and will be made available online for all NeuroTouch users allowing global comparison of neurosurgical performance.